Transformasi Digital dalam Perbankan Syariah: Meningkatkan Inklusi Keuangan Melalui Edukasi dan Literasi Digital - Eri Kusnanto; Muhammad Rizal; Ngadi Permana (Lembaga Pengembangan Kinerja Dosen, 2024)
This article explores the role of digital transformation in enhancing financial inclusion through Islamic banking, focusing on community digital education and literacy. The primary objective of this research is to empower communities with the necessary knowledge and skills to safely and effectively utilize digital Islamic banking services. This community service program was implemented through training, mentoring, and evaluation designed to increase understanding of Islamic fintech. The findings demonstrate a significant improvement in the comprehension and use of digital Islamic banking services, particularly in previously underserved areas. The study also highlights the importance of collaboration with local Islamic financial institutions to ensure that digital transformation can be inclusively implemented. This article is part of a broader effort to support the National Digital Economy Framework, emphasizing the importance of Islamic banking strategies in strengthening Indonesia's financial system and creating an inclusive and sustainable fintech ecosystem.